Financial risk and renewable energy: exploring the influence of urbanization and natural resource rents across 112 countries - Rongrong Li; Qiang Wang; Jiayi Sun (Humanities & Social Sciences Communications)
Abstract This study investigates the intricate relationship between financial risk and renewable energy consumption, incorporating the moderating effects of urbanization and natural resource rents. Utilizing a global panel dataset comprising 112 countries, the study applies econometric techniques, including fixed-effects models, moderation effect models, and panel threshold models, to investigate how varying levels of financial risk impact renewable energy consumption across diverse economic and environmental contexts. The results indicate that financial risk significantly suppresses renewable energy consumption, an effect that is further exacerbated by urbanization. At the same time, natural resource rents partially mitigate the adverse impact of financial risk. The moderating roles of both urbanization and natural resource rents jointly shape the overall effect of financial risk on renewable energy consumption. Additionally, the study identifies a single-threshold effect, where variations in urbanization and natural resource rents significantly influence the suppressive effect of financial risk. These findings emphasize the need for tailored financial strategies and urban planning policies to advance the global energy transition. The findings provide empirical support for policymakers seeking to balance economic stability with environmental sustainability, particularly in the context of emerging economies and regions heavily dependent on natural resources.